Peran guru dalam meningkatkan integrasi keilmuan siswa: Studi kasus SDN 1 Montong Baan - Ariatman, Roby; Ramdhani, Deddy (TAWAZUN: Jurnal Pendidikan Islam, 2024)
This study aims to examine the important role of teachers in improving scientific integration in students at SDN 1 Montong Baan. Using a qualitative research approach with a descriptive type. This study focuses on two research problem formulations first, how the role of teachers in improving students' scientific integration. Second, what are the challenges faced by teachers in the process of increasing scientific integration. Data were collected through in-depth interviews, participatory observation, and document analysis. The results showed that teachers play a key role in guiding students to understand the interrelationship between various disciplines, namely religion and science. The role of the teacher in improving students' scientific integration is as a demonstrator, facilitator, motivator, and learning resource in the learning process. The challenges faced by teachers in improving students' scientific integration include the lack of quality of teacher competence and the lack of teacher creativity in teaching. These findings emphasize the importance of teacher training in improving the quality and creativity of teacher teaching to support effective scientific integration for students. Abstrak Penelitian ini bertujuan untuk mengkaji peran penting guru dalam meningkatkan integrasi keilmuan pada siswa di SDN 1 Montong Baan. Menggunakan pendekatan penelitian kualitatif dengan jenis deskriptif. studi ini berfokus pada dua rumusan masalah penelitian pertama, bagaimana peran guru dalam meningkatkan integrasi keilmuan siswa. Kedua, apa saja tantangan yang dihadapi oleh guru dalam proses peningkatan integrasi keilmuan tersebut. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen. Hasil penelitian menunjukkan bahwa guru memegang peranan kunci dalam membimbing siswa untuk memahami keterkaitan antara berbagai disiplin ilmu, yakni agama dan sains. Adapun peran guru dalam meningkatkan integrasi keilmuan siswa ialah sebagai demonstrator, fasilitator, motivator, dan sumber belajar dalam proses pembelajaran. Tantangan yang dihadapi guru dalam meningkatkan integrasi keilmuan siswa di antaranya, kurangnya kualitas kompetensi guru dan kurangnya kreativitas guru dalam mengajar. Temuan ini menekankan pentingnya pelatihan guru dalam meningkatkan kualitas dan kreativitas mengajar guru untuk mendukung integrasi keilmuan yang efektif bagi siswa.